IGEM:Stanford/2010/Notebook/15 April 2010

From OpenWetWare

(Difference between revisions)
Jump to: navigation, search
(DNA-ligand binding)
(Journal Club 4/15/10)
Line 22: Line 22:
So we end up with:
So we end up with:
[DNA-L] = [TotalDNA][L] / (kD + L)
[DNA-L] = [TotalDNA][L] / (kD + L)
 +
 +
 +
===See also===
 +
 +
* [http://www.nature.com/nature/journal/v463/n7279/full/463301a.html Commentary on Danino et al.]

Revision as of 23:35, 15 April 2010

Journal Club 4/15/10

Presentation by ...

DNA-ligand binding

d[DNA-L]/dt = k_on*[DNA][L] - k_off*[DNA-L]

If we define: [TotalDNA] = [DNA] + [DNA-L]

Then: d[DNA-L]/dt = k_on*([TotalDNA] - [DNA-L]) - k_off*[DNA-L]

Solving, we get: [DNA-L] = [TotalDNA][L] / (k_off/k_on + L)

Usually, we define the dissociation constant to be: kD = k_off/k_on

So we end up with: [DNA-L] = [TotalDNA][L] / (kD + L)


See also

Personal tools